Morphological and molecular characterization of an equine isolate of Pythium insidiosum and comparison with the first human isolate from the same geographic region - Gimenes Bosco, Sandra de Moraes [UNESP]; Reis, Gabriela Martins [UNESP]; Theodoro, Raquel Cordeiro [UNESP]; Da Graca Macoris, Severino Assis [UNESP]; Marques, Silvio Alencar [UNESP]; Macoris, Delphim da Graca [UNESP]; Bagagli, Eduardo [UNESP] (Informa Healthcare, 2008)
Pythium insidiosum causes pythiosis, a life-threatening disease that occurs in tropical regions and affects man and animals. Although pythiosis in Brazil had been described in various animal species, the first human case was only recently reported. The present study aimed to characterize the morphologic and molecular characteristics of a new equine isolate of P. insidiosum and compare them with those of the first Brazilian human isolate. Both isolates were recovered from the same region of the country. Macroscopic and microscopic features were evaluated in two culture media. Sporangia formation and zoospore release were obtained after culturing the isolates with fragments of grasses and crops in an appropriate liquid induction medium. The molecular analysis of the isolates consisted of the complete sequencing of the ITS-5.8S rDNA region and sequences of both showed identical composition of 836 bp and 99% similarity with the isolates M16, 65, M12, 339 and 394 deposited at GenBank. Simple mycological procedures such as the production of sporangia and zoospores may distinguish P. insidiosum from zygomycetes. The rDNA sequencing indicates that, in Brazil, both humans and animals might be infected by a common genotype of the pathogen.
Keywords: Pythium insidiosum; pythiosis; ITS-5.8S rDNA; sporangia; zoospores